Flexible camphor diamond-like carbon coating on polyurethane to prevent Candida albicans biofilm growth. (April 2017) - Santos, Thaisa B.; Vieira, Angela A.; Paula, Luciana O.; Santos, Everton D.; Radi, Polyana A.; Khouri, Sônia; Maciel, Homero S.; Pessoa, Rodrigo S.; Vieira, Lucia
Abstract: Camphor was incorporated in diamond-like carbon (DLC) films to prevent the Candida albicans yeasts fouling on polyurethane substrates, which is a material commonly used for catheter manufacturing. The camphor:DLC and DLC film for this investigation was produced by plasma enhanced chemical vapor deposition (PECVD), using an apparatus based on the flash evaporation of organic liquid (hexane) containing diluted camphor for camphor:DLC and hexane/methane, mixture for DLC films. The film was deposited at a low temperature of less than 25 °C. We obtained very adherent camphor:DLC and DLC films that accompanied the substrate flexibility without delamination. The adherence of camphor:DLC and DLC films on polyurethane segments were evaluated by scratching test and bending polyurethane segments at 180°. The polyurethane samples, with and without camphor:DLC and DLC films were characterized by Raman spectroscopy, scanning electron microscopy, atomic force microscopy, and optical profilometry. Candida albicans biofilm formation on polyurethane, with and without camphor:DLC and DLC, was assessed. The camphor:DLC and DLC films reduced the biofilm growth by 99.0% and 91.0% of Candida albicans, respectively, compared to bare polyurethane. These results open the doors to studies of functionalized DLC coatings with biofilm inhibition properties used in the production of catheters or other biomedical applications. Highlights: Camphor:DLC film to avoid Candida albicans biofilm growth. Flexible DLC containing camphor on polyurethane substrate. DLC film with terpenoid radical from camphor identified by Raman maps.